Pengaruh Human Capital terhadap Positive Organizational Behavior Pegawai Divisi Marketing di BUMN Bidang Jasa Wilayah Jawa Barat - Anissa L. Kadiyono (Universitas Padjadjaran, 2011)
This study investigates the meaning of employee as human capital in organization. Drawing form positive psychology movements, the main purpose of the research is to analyze the influences of human capital to Positive Organizational Behavior. The value-added contribution that organizational member can achieve organizational effectiveness is Positive Organizational Behavior. What capacities should employees develop that will make them more productive and provide competitive advantages in today’s turbulent environment is human capital. Human Capital (Petterson & Spiker) is an individual asset as employee who has knowledge, experience, skills, attitude, value, and other personal attributes that have contribury value on organization. Positive Organizational Behavior based on Luthans is the study and application of positive oriented human resource strengths and psychological capacities that can be measured, developed, and effectively managed for performance improvement in today's workplace. Using Lisrel software, a confirmatory factor analysis was conducted using maximum likelihood techniques and replicated the second order factor structure. Specifically, this analysis conducted confirmatory factor analytic model comparisons to determine the statistically best performing measurement model. Sample size is 452 person, has been taken from marketing division in The State-Owned Enterprises of Services Industry in West Java. They are PT. Telekomunikasi Indonesia, Tbk., PT. Pos Indonesia (Persero), PT. PLN (Persero), and PT. Industri Telekomunikasi Indonesia (Persero). The hypothesis indicated that there is significant influences of Human Capital to Positive Organizational Behavior at Marketing Division Employees in The State Owned Enterprises of Services Industry in West Java.*****Penelitian ini dilakukan untuk mengungkapkan peran pegawai di perusahaan dalam konsep human capital. Berlandaskan gerakan psikologi positif, maka penelitian ini berupaya meneliti apakah Human Capital memegang peranan dalam mempengaruhi Positive Organizational Behavior pegawai yang merupakan cerminan upaya pegawai dalam mencapai tujuan organisasi. Konsep Human Capital yang digunakan menggunakan konsep yang dikemukakan oleh Petterson dan Spiker yang menyatakan bahwa human capital adalah aset individu selaku pegawai yang berisikan pengetahuan, pengalaman, keterampilan, sikap, nilai dan atribut personal lainnya yang memiliki nilai tambah bagi organisasi. Positive Organizational Behavior menggunakan konsep yang dikemukakan oleh Luthans, yaitu pengaplikasian potensi individu selaku sumber daya manusia yang memiliki potensi dan kapasitas psikologis yang dapat diukur, dikembangkan, dan dikelola untuk mengembangkan performansi kerja di tempat kerjanya. Pengujian hipotesis penelitian menggunakan Structural Equation Model dengan metode Second Order Confirmatory Factor Analysis dengan Maximum Likelihood Techniques. Metode penelitian yang digunakan bersifat deskriptif dan exsplanatory survey terhadap unit sampel sebesar 452 orang pegawai divisi marketing di BUMN bidang Jasa di wilayah Jawa Barat, yaitu PT. Telekomunikasi Indonesia, Tbk., PT. Pos Indonesia (Persero), PT. PLN (Persero), dan PT. Industri Telekomunikasi Indonesia (Persero). Hasil pengujian hipotesis menunjukkan bahwa terdapat pengaruh Human Capital terhadap Positive Organizational Behavior pada pegawai divisi marketing pada BUMN bidang jasa di wilayah Jawa Barat.